Adsorption and affinity of Escherichia coli to different aggregate sizes of a silty clay soil - Behrends Kraemer, Filipe (2013)
The sediments produced by water erosion are the main source of pollution of agricultural origin of surface water bodies. These sediments may be associated to bacteria, compromising the quality of nearby water bodies. Therefore, to understand this biological contamination, it is necessary to find out the adsorption capacity and bacterial affinity to aggregate sizes that may result in a differential sedimentation. To this end, in the present work, the distribution, adsorption capacity and affinity to different aggregate sizes of two strains of Escherichia coli in two liquid media of contrasting ionic strength were evaluated in a silty clay soil. The <2 μm fraction showed a higher proportion of bacteria than the other aggregate sizes (48%), whereas among the fractions >2 μm, the 20-50 μm fraction was the one that showed the highest bacterial adsorption in both liquid media (37.9%). On the other hand, the highest values of bacterial affinity were found in the 20 to 50 μm fraction (coarse silt) in the low ionic strength media and 20-50 and >50 μm in the high ionic strength media. However, the bacterial strains used revealed only some trends in the modification of these variables. This work contributes to the development and implementation of strategies to mitigate pollution, such as control of sediment generation and its subsequent capture in filter strips.